STUDENTS’ MOTIVATION ON WRITING HORTATORY EXPOSITION BY USING POW PLUS TREE STRATEGY AT SMAN1 BUKIT BATU - Aprizawati Aprizawati (Politeknik Negeri Bengkalis, 2017)
Abstract: The purpose of this research was to find out students’ writing motivation in hortatory exposition by using POW plus TREE strategy. The research was carried out at the eleventh grade students at SMAN 1 Bukit Batu This research was quantitative research. The population in this study was 26 students who were taken randomly. A set of questionnaire was distributed to 26 students regarding their motivation on writing hortatory exposition by using POW plus TREE strategy. In this research, measurement of these statements using 30 statements in questionnaire based on indicators to assess students’ motivation in writing hortatory exposition. The data collected was analyzed using SPSS 22 to know the normality, validity, and reliability of the instrument. The researcher measured the total score from the result of the students’ motivation in writing ability test. The results of this study showed that students had goodmotivation in writing hortatory exposition by using POW plus TREE strategy. Keywords: Motivation, writing, hortatory exposition, POW plus TREE.